2017
DOI: 10.2136/sssaj2017.06.0198
|View full text |Cite
|
Sign up to set email alerts
|

Use of the USDA National Cooperative Soil Survey Soil Characterization Data to Detect Soil Change: A Cautionary Tale

Abstract: Recently, the USDA-NRCS National Cooperative Soil Survey Soil Character ization Database (NSCD) was reported to provide evidence that total nitrogen (TN) stocks of agricultural soils have increased across the Mississippi basin since 1985. Unfortunately, historical changes in methods used to mea sure TN were not fully accounted for in that report. We used NSCD archives to calibrate between wet (pre1995) and dry (post1995) digestion methods used in measuring TN and soil organic carbon (SOC), then evaluated tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Owusu et al (2020) described the soil sampling scheme adopted for the pedon characterization and the limitations of such long‐term datasets. In essence, these national soil survey datasets serve as a reservoir of soil information that basically provides a set of snapshot evidence about soil properties (Tomer et al, 2017). Nevertheless, the pedons were sampled in diverse geomorphic areas and land use types.…”
Section: Methodsmentioning
confidence: 99%
“…Owusu et al (2020) described the soil sampling scheme adopted for the pedon characterization and the limitations of such long‐term datasets. In essence, these national soil survey datasets serve as a reservoir of soil information that basically provides a set of snapshot evidence about soil properties (Tomer et al, 2017). Nevertheless, the pedons were sampled in diverse geomorphic areas and land use types.…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, the understanding of soil N content and its changes on a large spatial scale require extensive soil geochemical surveys. The high costs and low efficiency of soil surveys, commonly done by field sampling, remain a significant restriction on monitoring and mapping soil properties [12][13][14]. Therefore, it is necessary to develop and optimize more economical and effective techniques to estimate and map the N content of topsoil on a regional or even larger scale.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages to agricultural producers, the long‐term usage of CS rotation potentially jeopardizes soil health and crop production by altering the soil microbial activities and other soil properties. Previous studies demonstrated that long‐term use of CS rotation led to decline in soil organic C (Drinkwater et al., 1998), reduction in soil reactive N (Hall et al., 2019; Tomer et al., 2017), loss of soil aggregate stability (Zuber et al., 2015), and reduction in crop yield (Smith et al., 2008). Moreover, CS rotation can potentially reduce bacterial richness and diversity (Venter et al., 2016; Zhou et al., 2015) and fungal biodiversity and abundance (Ding et al., 2017), meanwhile posing the risk of long‐term soil degeneration (Katsvairo & Cox, 2000; Yin et al., 2015).…”
Section: Introductionmentioning
confidence: 99%